The Health Education Models in Reducing Child Mortality Rate of Vulnerable Communities - Jose Dionisio Ximenes; Joaquim Pinto; Eduardo C Gaio; Maria Manuela Alves (Medical Studies and Health Journal (SEHAT), 2024)
Culturally adapted health education plays a crucial role in reducing child mortality in vulnerable communities with diverse cultural backgrounds. This article conducts a systematic review of existing literature to evaluate the effectiveness of health education models adapted to local cultural contexts. Through a systematic literature review approach, this research identifies and synthesizes scientific evidence regarding the impact of cultural adaptation models on child health outcomes. Key findings show that interventions that take into account community-specific cultural values ​​and practices have a significant positive impact on reducing child mortality. However, the effectiveness of this model is highly dependent on the extent to which cultural elements are integrated in health education strategies and implementation contexts. This article provides practical implications for policy makers, health practitioners, and researchers, and identifies research gaps that need further exploration. Recommendations for future research include longitudinal studies, broader context-based research, and integration of qualitative methods to increase understanding of cultural adaptation in health education.